Dependence of light yield of scintillation strips on the reflective coating material kind - Melnichuk, S.V. (Functional Materials, 2004)
Effect of the coating material on the reflection factor and light yield of scintillation strips has been studied. The light yield dependences on the pigment type, its concentration, and the coating material preparation techniques have been investigated. A novel method has been developed and realized to introduce a powdered pigment into polymer matrix at high pigment concentrations. This technique has been shown to provide co-extruded scintillation strips with the light yield up to 9 ph.el. (exceeding about by 40 % the foreign analogs). Проведено изучение влияния вида покрытия на коэффициент отражения и световой выход сцинтилляционных стрипов. Исследованы зависимости светового выхода от типа пигмента, его концентрации и способа получения материала покрытия. Разработан и реализован новый метод введения порошкового пигмента в полимерную матрицу в больших концентрациях. Показано, что это позволило получать соэкструзионные стрипы, которые имеют световой выход до 9 ф.э. (на 40 % больше, чем аналоги мировых производителей). Проведено вивчення впливу типу покриття на коєфіцієнт відбиття та світловий вихід сцинтиляційних стрипів. Досліджено залежність світловиходу стрипів від типу пігмента, його концентрації та способу отримання матеріалу покриття. Розроблено та реалізовано новий спосіб введення порошкового пігменту у покриття у великих концентраціях. Показано, що це дозволило отримувати коекструзійні стрипи, що мають світловий вихід до 9 ф.е. (на -40 % більше, ніж світові аналоги).